2023
DOI: 10.1126/sciadv.adf9299
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shallow megathrust afterslip from the 2021 M8.2 Chignik, Alaska earthquake revealed by seafloor geodesy

Abstract: The shallower portions of subduction zone megathrust faults host Earth’s most hazardous tsunamigenic earthquakes, yet understanding how and when they slip remains elusive because of challenges making seafloor observations. We performed Global Navigation Satellite System Acoustic seafloor geodetic surveys before and ~2.5 months after the 29 July 2021 M w (moment magnitude) 8.2 Chignik, Alaska, earthquake and determine ~1.4 meters cumulative co- and post-seismic horizontal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…In this study the earthquake we observed had a primarily deep rupture that was verified by the small offset at the seafloor GNSS‐A site. In comparison, other studies have identified cases where coseismic slip greater than 1 m did extend to shallow depths, such as has been observed for the Chignik (Brooks et al., 2023) and Tohoku (Kido et al., 2011; Sato et al., 2011a) earthquakes. Thus, even though this study confirms previously published models of the Simeonof earthquake (Crowell & Melgar, 2020; Liu et al., 2020; Ye et al., 2021), the seafloor geodetic measurements are necessary to understand the shallow slip behavior in subduction zone earthquakes.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study the earthquake we observed had a primarily deep rupture that was verified by the small offset at the seafloor GNSS‐A site. In comparison, other studies have identified cases where coseismic slip greater than 1 m did extend to shallow depths, such as has been observed for the Chignik (Brooks et al., 2023) and Tohoku (Kido et al., 2011; Sato et al., 2011a) earthquakes. Thus, even though this study confirms previously published models of the Simeonof earthquake (Crowell & Melgar, 2020; Liu et al., 2020; Ye et al., 2021), the seafloor geodetic measurements are necessary to understand the shallow slip behavior in subduction zone earthquakes.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, there was not a large tsunami that such a displacement would likely have produced. Another hypothesis is that the offset at IVB1 is primarily postseismic rather than coseismic, as was inferred at the SEM1 array following the neighboring Chignik earthquake in 2021 (Brooks et al., 2023). However, this hypothesis would also yield a rupture model with little shallow slip similar to the one we present in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To mitigate the error caused by poorly constrained sound speed, Spiess (1985) outlined a method in which only the assumptions of thermal stratification and rigid block motion are required: acoustic ranging to a symmetric array of seafloor transponders will determine the array's horizontal center with high precision, forcing uncertainty in sound speed to impact only the vertical component of the array if it moves as a rigid block. Based on this method, GNSS‐A has been successfully applied to a number of seafloor geodesy projects, yielding centimeter or better precision in horizontal seafloor positioning (e.g., Gagnon et al., 2005; Chadwell & Spiess, 2008; Tomita et al., 2017; Yokota & Ishikawa, 2020; Brooks et al., 2023). The method, though proven effective, requires at least three transponders to form an array, limiting the array's reliability and number of equivalent sites (e.g., three transponders to form an equilateral triangle array, four transponders to form a square array, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Seafloor geodetic data have been shown to increase resolution of geodetic studies in subduction zone regions (Iinuma et al., 2012; Tomita et al., 2020; Yokota et al., 2016), and it is anticipated that the addition of GNSS‐A sites will enable better recovery of slip distributions at subduction zones (Bürgmann & Chadwell, 2014; Sathiakumar et al., 2017). These instruments are placed on the seafloor, very close to the trench (Brooks et al., 2023)—that is, in a region with very significant bathymetry that is likely to bias slip estimates unless it is accounted for.…”
Section: Introductionmentioning
confidence: 99%